2006
DOI: 10.1074/jbc.m608853200
|View full text |Cite
|
Sign up to set email alerts
|

Study of Claudin Function by RNA Interference

Abstract: Claudins are tight junction proteins that play a key selectivity role in the paracellular conductance of ions. Numerous studies of claudin function have been carried out using the overexpression strategy to add new claudin channels to an existing paracellular protein background. Here, we report the systematic knockdown of endogenous claudin gene expression in Madin-Darby canine kidney (MDCK) cells and in LLC-PK1 cells using small interfering RNA against claudins 1-4 and 7. In MDCK cells (showing cation selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
183
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(204 citation statements)
references
References 32 publications
19
183
0
2
Order By: Relevance
“…Thus, the proteinaceous TJ strands are dominantly responsible for the paracellular barrier functions, consistent with the dominant contribution of TJs, compared with the minor contribution of the lateral intercellular space, to paracellular resistance that was revealed by physiological measurements (Kottra et al, 1993a; Kottra and Fro¨mter, 1993b; Yap et al, 1998). Second, transfection or knockdown of individual claudins or their combinations in cultured epithelial cells led us to speculate that claudin-2 and -15 contribute to cation channels/pores Van Itallie et al, 2003), whereas claudin-4, -7 and -10a contribute to anion channels/pores or cation barriers (Hou et al, 2006;Van Itallie et al, 2006b) (Figure 3). The plus or minus charges of the first loops of claudin molecules thus appear to have functions in paracellular epithelial permeation (Colegio et al, 2003).…”
Section: Mysterious Molecular Mechanisms Of Tj Physiology Implied By mentioning
confidence: 88%
“…Thus, the proteinaceous TJ strands are dominantly responsible for the paracellular barrier functions, consistent with the dominant contribution of TJs, compared with the minor contribution of the lateral intercellular space, to paracellular resistance that was revealed by physiological measurements (Kottra et al, 1993a; Kottra and Fro¨mter, 1993b; Yap et al, 1998). Second, transfection or knockdown of individual claudins or their combinations in cultured epithelial cells led us to speculate that claudin-2 and -15 contribute to cation channels/pores Van Itallie et al, 2003), whereas claudin-4, -7 and -10a contribute to anion channels/pores or cation barriers (Hou et al, 2006;Van Itallie et al, 2006b) (Figure 3). The plus or minus charges of the first loops of claudin molecules thus appear to have functions in paracellular epithelial permeation (Colegio et al, 2003).…”
Section: Mysterious Molecular Mechanisms Of Tj Physiology Implied By mentioning
confidence: 88%
“…Evidence in vitro suggests that claudins are essential for the paracellular barrier formation. Expression of claudins is sufficient to form TJ strands in fibroblasts, and disruption of claudins decreases the paracellular barrier properties of canine kidney cells (Furuse et al 1998(Furuse et al , 2001Van Itallie et al 2001;Amasheh et al 2005;Hou et al 2006). Work with chimeric claudins has shown that amino acid residues in the first extracellular loop define the size and charge selectivity of the pore within the cellular junction, and, thus, the composition of the claudins within a given cell can determine the permeability of the paracellular barrier (Colegio et al 2003).…”
Section: Tight Junctionsmentioning
confidence: 99%
“…It is important to recognize that a claudin that acts as a selective pore to one population of ions must, by definition, constitute a relative barrier to all other ions; that this function is manifest may depend on the host cell. For example, Hou et al (43) used small interfering (si) RNA to knock down endogenous claudins in epithelial cells and found that claudin-4 and claudin-7 act as cation barriers in MDCKII cells while forming anion-selective pores in LLC-PK 1 cells (43).…”
Section: Physiological Function Of Claudinsmentioning
confidence: 99%